Photocatalytic degradation studies of organic dyes over novel Ag-loaded ZnO-graphene hybrid nanocomposites. (January 2021) - Beura, Rosalin; Pachaiappan, Raman; Paramasivam, Thangadurai
Abstract: A nanocomposite of Ag-impregnated ZnO-graphene (GZAg) has been prepared by a hydrothermal method. Hexagonal structured ZnO nanorods decorated with cubic structured Ag nanoparticles have been characterized therein. Raman scattering experiments confirmed the presence of graphene in the nanocomposite. Microstructure analysis by TEM showed that the nanorods of ZnO decorated with Ag nanoparticles were well embedded within the graphene sheets. Band-gap energies were measured in the range from 3.19 to 3.04 eV, and the PL lifetime was seen to decrease with increasing Ag content. Photocatalytic studies have been conducted on methyl orange (MO) dye under UV light and sunlight in the presence of the GZAg photocatalysts. Those with lower Ag contents (0.5 and 3 wt%) showed greater degradation of MO. Degradation efficiencies as high as 96% and 98% were achieved under UV light and sunlight, respectively, much higher than those over the undecorated graphene-ZnO. Photocatalytic experiments have been conducted under different conditions, such as at different pH values and with mixed dyes. MO was degraded most efficiently in an acidic medium, and its degradation mechanism is discussed in terms of the band diagram. The best photocatalytic activity was achieved through a combination of optimum Ag loading, increased generation of · OH radicals, increased absorption of visible light and increased charge transfer to inhibit recombination. Graphical abstract: Image 1 Highlights: Ag-impregnated ZnO-graphene nanocomposites have been prepared by a hydrothermal method. The photocatalytic activities of these nanocomposites have been tested on methyl orange under UV irradiation and sunlight. A maximum of 98% degradation was achieved, twice as rapidly under sunlight than under UV light. Radical scavenging tests confirmed the dominant role of · OH radicals. Mechanistic and pH-dependent studies of the photocatalysis have been conducted.